Bacillus subtilis strain BS06 protects soybean roots from Fusarium oxysporum infection. Issue 15 (9th August 2021) - Jia, Yujing; Huang, Jingxin; Qi, Lanlan; Zhang, Xiaole; Liu, Jianhong; Guan, Huilin; Wang, Chenjiao; Tang, Guangmei; Dou, Xiaolin; Lu, Meng
ABSTRACT: Soybean, as a major oil crop, is one of the most widely planted crops in the world. Fusarium oxysporum causes soybean root rot, leading to great economic losses to soybean planting every year globally. Chemical fungicide for controlling soybean F. oxysporum diseases may cause environmental problems and has human health risks. Biological control methods avoid these shortcomings; however, few studies have focused on biocontrol of soybean diseases caused by F. oxysporum . Aiming at this problem, we obtained biocontrol bacteria against soybean F. oxysporum by plate confrontation method. The type of the strain with the highest biocontrol activity was identified by molecular biological methods, and then its biocontrol effects were verified through greenhouse experiments. One of our isolated strain named BS06 strain had the highest activity, which was identified as Bacillus subtilis . Our study showed that BS06 strain could effectively control soybean F. oxysporum disease and significantly reduce F. oxysporum to infect soybean roots. Compared with control and carbendazim treatments, BS06 treatment had higher root biomass, plant height, leaf chlorophyll content, stem base diameter and control efficiency. Our results indicated that BS06 could effectively protect soybean root (BS06 strain might produce substances to inhibit  F. oxysporum ), which was potentially useful for soybean planting. Abstract : We found that a Bacillus subtilis strain could control soybean Fusarium oxysporum disease, which was usually reported to be harmless to humans and the environment.